Preparation and characterization of zinc oxide nanoparticles - Baharudin, Khairul Basyar (2011)
Zinc oxide nanoparticles are important inorganic particles which receive great interest over the past few years because of the wide nanotechnology application in various fields of material physics and chemistry. The physicochemical properties of resulting ZnO nanoparticles can be controlled by the synthesis route, method of preparation and parameters related to condition processing. In this study, ZnO nanoparticles were successfully synthesized by three different methods namely polyol method, solvothermal method and co-precipitation method. X-ray diffraction (XRD) patterns show that the all resulting ZnO nanoparticles materials which were synthesized by all the three different methods are pure phase with good crystalinity and completely matched the hexagonal-wurzite structure. The presence of a broad and sharp absorption band at around 440 cm-1 in the FTIR spectrum further confirmed the existence of ZnO phase. In polyol method, ZnO nanoparticles were successfully synthesized under hydrothermal condition. Zinc acetate (ZnAc) was dissolved and heated in three different glycol solutions, namely ethylene glycol (EG), diethylene glycol (DEG) and trietyleneglycol (TEG). The effect of different glycol solutions and calcination on the formation of ZnO nanoparticles was investigated. Single-modal narrow particle size distribution of ZnO nanoparticles with average particles size of 2 ± 1 nm, 12 ± 1nm and 13 ± 1 nm were obtained when EG, DEG and TEG were used in the synthesis, respectively. The broadness of the size distribution of the ZnO nanoparticles can be given as EG > DEG >TEG. The specific surface areas of all the resulting materials however show very similar values ranging from 12.2 to 13.5 m2g-1. The low-temperature solvothermal process was employed as the second method to synthesize ZnO nanoparticles. The initial concentration of zinc acetate was controlled and this process is based on the decomposition of zinc acetate and sodium hydroxide (NaOH) in a mixture solution of ethanol and EG. The effect of different zinc acetate concentration and the effect of organic solvent mixtures solution between ethanol and EG can be shown by a single modal narrow particle size distribution with the average size below 25 ± 1 nm. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis revealed that less macroscopic agglomeration of ZnO nanoparticles, indicating that the effect of low temperature process in the mixtures solution also contributed to the higher specific surface area of about 40 m2g- 1. Further effect of high calcinations temperature on the physicochemical properties of the resulting ZnO nanoparticles shows more crystalline and pure phase. However, the increasing particles size resulted in the decreasing of specific surface area due to the compact agglomeration of ZnO particles. Lastly, an intermediate zinc oxalate phase was synthesized by oxalate coprecipitation from nearly saturated solution of zinc acetate and 2-propanol of oxalic acid solution. Highly crystallized and pure phase ZnO nanoparticles were successfully synthesized by thermal treatment at 400 to 600 oC for 4 hours. Single-modal narrow particle size distribution of ZnO nanoparticles with the average particles size of 3± 1 nm , 28 ± 1 nm and 25 ± 1 nm are obtained at 400, 500 and 600 oC, respectively. FESEM and TEM also revealed the different surface structure and morphology of ZnO nanoparticles obtained at calcination temperatures. A huge reduction of specific surface area of ZnO nanoparticles from 22.9 m2g-1 to 2.6 m2g-1 was observed when the calcination temperature is increased from 400 to 600 oC. This study verified, a good crystallinity, high purity, small particle size and large specific surface area of ZnO nanoparticles can be obtained using all the methods. The effect of preparation parameters in each method gives the most influence to physichochemical properties of the resulting material.